(Invited) Solution Exfoilated Black Phosphorus and Its Applications. (3rd May 2017) - Lin, Shenghuang; Lau, Shu Ping
Abstract : Black phosphorus (BP), has recently attracted much attention all over the world and demonstrated great potential in novel nanoelectronics owing to its direct and narrow bandgap. Regarding to the scale production of BP and its related electronic devices, solution exfoliation reveals superior advances when compared with mechanical exfoliation. Remarkably, liquid-phase exfoliated BP flakes and quantum dots (QDs) exhibit exciting properties in solar cells, electronic, and optical devices. The exfoliation of BP in diverse solvents have been demonstrated. The solution exfoliated BP flakes can be an effective electron transport layer in organic photovoltaics (OPVs). The BP QDs can be incorporated in the active layer of OPV to enhance its power conversion efficiencies. In addition, the BP flakes exhibit nonlinear optical properties which can be an excellent saturable absorber for high energy pulse generation in fiber laser.